2000
DOI: 10.1097/00004347-200004000-00004
|View full text |Cite
|
Sign up to set email alerts
|

The Patterns of Expression of an Apoptosis-Related CK18 Neoepitope, the bcl-2 Proto-Oncogene, and the Ki67 Proliferation Marker in Normal, Hyperplastic, and Malignant Endometrium

Abstract: Expression of a neoepitope on cytokeratin 18, recognized by the monoclonal antibody M30, is an early indicator of apoptosis in epithelial cells. The aim of this study was to determine the equilibrium between apoptosis (M30), anti-apoptosis (bcl-2), and proliferation (Ki-67) in different endometrial conditions. Paraffin-embedded samples (n = 107), representing proliferative endometrium (18), secretory endometrium (19), postmenopausal endometrium (15), disordered proliferative endometrium (6), simple hyperplasia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0
4

Year Published

2001
2001
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 26 publications
3
43
0
4
Order By: Relevance
“…Many studies have revealed that tissue degradation associated with menstruation is the result of an active process in which apoptosis is involved [5,[8][9][10]. Studies performed in vitro and in transgenic mice indicate that Bcl-2 could play a role in extending the survival of normal and pathologic cells by preventing apoptosis [5,[8][9][10][11]15]. Bcl-2 can inhibit the apoptosis induced by cmyc [1].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Many studies have revealed that tissue degradation associated with menstruation is the result of an active process in which apoptosis is involved [5,[8][9][10]. Studies performed in vitro and in transgenic mice indicate that Bcl-2 could play a role in extending the survival of normal and pathologic cells by preventing apoptosis [5,[8][9][10][11]15]. Bcl-2 can inhibit the apoptosis induced by cmyc [1].…”
Section: Discussionmentioning
confidence: 99%
“…The histologic appearance of the endometrium was classified as M = menstruation (days 1-5), EP = early proliferative (days 6-9), LP = late proliferative (days [10][11][12][13][14], ES = early secretory (days [15][16][17][18], MS = mid-secretory (days [19][20][21][22] and LS = late secretory (days 23-28) phase. For each of these phases specimens from 5 representative uteri were collected.…”
Section: Uterine Tissue Samplesmentioning
confidence: 99%
See 2 more Smart Citations
“…14 Studies have also shown that Ki-67 proliferation indices are increased in numerous human malignancies, including high-grade endometrial cancer, as compared with post-menopausal (atrophic) endometrium. 15 High proliferation indices with Ki-67 are also seen in invasive 7,16 and intraepithelial serous carcinoma. 12 In contrast, our findings show that the majority of atypical tubal metaplasia is either negative for Ki-67 or shows a low proliferation index, with Ki-67 immunopositivity limited to less than 5% of atypical cells.…”
Section: Ki-67mentioning
confidence: 99%